"If we didn't talk, we would be like ostriches burying our heads in the sand": Attitudes toward sexuality, gender, and sex education among child protection social workers in Egypt. (October 2021) - Riad, Germeen; Forden, Carie
Highlights: Egyptian social workers need to provide sexual and reproductive health education. Misconceptions about sexuality, gender stereotypes, and misinformation were common. They view sexual and reproductive health education as important and want training. Training should include both accurate information and exploration of personal values. Abstract: The incidence of sexual and gender-based violence, including child marriage, female genital mutilation/cutting, virginity testing, sexual harassment, and child sexual abuse, is high in Egypt. Child protection social workers must deal with children who have been victims of such practices and must provide the sex education that is necessary for its prevention, but the "culture of silence" that surrounds sexuality in Egypt may make this difficult. A survey of 86 child protection social workers and 11 semi-structured interviews were conducted in order to better understand how they viewed and dealt with sexuality, sexual and reproductive health education, gender roles, and sexual and gender-based violence. Analysis of both the survey and interviews revealed that most of the research participants strongly believed in the importance of sexuality education. However, they also held misconceptions about masturbation, menstruation, men's ability to control sexual desire, virginity and sensitivity of female reproductive organs, as well as gender stereotypes that supported gender-based violence and gender inequality. Based on these results, recommendations are made for culturally appropriate training to build social workers' capacity for addressing sexuality and gender issues in their child protection practice.